2009
DOI: 10.1007/s10639-009-9105-0
|View full text |Cite
|
Sign up to set email alerts
|

South Africa’s readiness to integrate ICT into mathematics and science pedagogy in secondary schools

Abstract: One of South Africa's identified priorities is the implementation of ICT in education. To this end a phased implementation plan was initiated in 2004 for ICT to be implemented into schools across the country over eight years. During this time South Africa also participated in three international studies undertaken by the International Association for the Evaluation of Educational Achievement (IEA) focusing on ICT in Education. Each of these permitted the country to benchmark its progress in terms of other coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 5 publications
5
18
0
1
Order By: Relevance
“…Our results agree with the results of other similar studies showing the positive outcomes of a computer-based model of teaching mathematical concepts (Dimakos & Zaranis, 2010;Howie & Blignaut, 2009;Starkey, Klein, & Wakeley, 2004;Papadakis et al, 2016b;Trouche & Drijvers 2010;Zaranis et al, 2013). Therefore, the fourth research question was also answered positively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with the results of other similar studies showing the positive outcomes of a computer-based model of teaching mathematical concepts (Dimakos & Zaranis, 2010;Howie & Blignaut, 2009;Starkey, Klein, & Wakeley, 2004;Papadakis et al, 2016b;Trouche & Drijvers 2010;Zaranis et al, 2013). Therefore, the fourth research question was also answered positively.…”
Section: Discussionsupporting
confidence: 92%
“…The results of various studies link the appropriate use of computers with the ability of students to more effectively understand various mathematical concepts (Howie & Blignaut, 2009;Trouche & Drijvers, 2010;Walcott et al 2009). A large number of studies show a positive correlation between using computers and the development of mathematical thinking in school (Clements, 2002;Papadakis, Kalogiannakis, & Zaranis, 2016b;Vale & Leder, 2004).…”
Section: Ict and Rmementioning
confidence: 99%
“…The national goals for integrating ICT in South African schools are summarised by Howie, Muller and Patterson (2005) and Howie and Blignaut (2009). In 2007, a baseline survey was conducted (Farrell & Isaacs, 2007) for the Department of Education (DoE) to determine the ICT available in schools in order to make informed decisions in terms of resource allocation.…”
Section: South Africamentioning
confidence: 99%
“…At the national level, the Indian government has been equipping rural regions with towers and ICT facilities in schools (Mathur & Sharma, 2009); a trend also observed in other developing countries like South Africa (Howie & Blignaut, 2009;Howie, 2010). It is suggested that if developing countries like India could address the factors that influence technology adoption, access and quality of education could be drastically improved in rural and impoverished regions (Lee, 2005;Feder, 1985).…”
Section: Access and Equitymentioning
confidence: 99%
“…Much like in the case of India, where the government has been investing in equipping rural regions with towers and schools with ICT facilities (Mathur & Sharma, 2009), the South African government has also been working on making ICTs an integral part of classroom learning (Howie & Blignaut, 2009), with the introduction of initiatives such as the technology-enhanced learning initiative (TELI), SchoolNet and Gauteng and Khanya projects. In addition, a…”
Section: Different Teachers Would Be Able To Take Out Different Thingmentioning
confidence: 99%